Structure of one class of groups with conditions of denseness of normality for subgroups - Semko, N. N. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We give a constructive description of locally graded groups G satisfying the following condition: For any pair of subgroups A and B such that A